USE OF MARKETING CONCEPTS IN THE ACTIVITY OF ORGANIZATIONS IN THE CONDITIONS OF FORMING AN INNOVATIVE ECONOMY - Rakhmonova Feruza Musakulovna; Komilova Mukammal Shavkatovna; Shernazarov Temurbek Tulkinovich (Scholar Express Journals, 2022)
This article describes the ways to use modern marketing concepts in the activities of enterprises in the formation of an innovative economy.
Keywords: Innovation; Competition; Marketing; Concept